2005
DOI: 10.1080/01972240590925320
|View full text |Cite
|
Sign up to set email alerts
|

Weak Ties in Networked Communities

Abstract: Abstract. Communities with high levels of social capital are likely to have a higher quality of life than communities with low social capital (Coleman, 1988(Coleman, , 1990Putnam, 1993Putnam, , 2000. This is due to the greater ability of such communities to organize and mobilize effectively for collective action because they have high levels of social trust, social networks, and well-established norms of mutuality (the major features of social capital). Communities with 'bridging' social capital (weak ties acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
157
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 269 publications
(175 citation statements)
references
References 20 publications
14
157
0
4
Order By: Relevance
“…These teachers also have higher degrees of centrality in indirect relations and in conversational networks, so the fact of belonging to more than one community expands the number of relations they establish, providing them with more information. These findings ratify the results of previous studies which demonstrated the prominent role of bridging people in sustaining higher rates of communication (Schlager et al, 2009) or community involvement and social engagement (Kavanaugh, Reese, Carroll, & Rosson, 2005). According to Kavanaugh et al (2005), communities that have people acting as bridges, as well as strong ties within groups, can better collaborate and their production is more effective.…”
Section: Rq2: Do Teachers' Network Have Particular Properties and Chsupporting
confidence: 81%
“…These teachers also have higher degrees of centrality in indirect relations and in conversational networks, so the fact of belonging to more than one community expands the number of relations they establish, providing them with more information. These findings ratify the results of previous studies which demonstrated the prominent role of bridging people in sustaining higher rates of communication (Schlager et al, 2009) or community involvement and social engagement (Kavanaugh, Reese, Carroll, & Rosson, 2005). According to Kavanaugh et al (2005), communities that have people acting as bridges, as well as strong ties within groups, can better collaborate and their production is more effective.…”
Section: Rq2: Do Teachers' Network Have Particular Properties and Chsupporting
confidence: 81%
“…Bridges are, at the most basic level, members of two or more distinct community organizations (Kavanaugh et al, 2005). In a scientific community, bridges are researchers who are part of two or more research communities (e.g., HCI and IS: Information Systems).…”
Section: Visualize Query-based Social Networkmentioning
confidence: 99%
“…Second, it facilitates communication (Carley, 1991;Mayhew et al, 1995) and sharing of resources (Adler and Kwon, 2002;Kavanaugh et al, 2005;Putnam, 2001) among members of the same group. Third, it fosters individuals' group loyalty and contributes to the stability of social ties with other group members (Brewer, 1979;Van Vugt and Hart, 2004).…”
Section: In-group Identity Preferencementioning
confidence: 99%